DESAIN DAKWAH SAYID IDRUS DI SULAWESI TENGAH - Siame, Norma Dg.; Samsinas, Samsinas (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 11 No 1 (2015), 2015)
Sayyid Idrus is a preacher in modern era in 1929. This era is also known as a period in which an idea of Islamic renewal had flourished in the Muslim world. It is not surprising that an idea of Islamic renewal has also influenced  Sayyid  Idrus's thought and preaching design, which in turn has a significant impact on the people of Palu in particular,  and  Central Sulawesi in general.  This paper used historical analysis  with science  of  da'wah  approach.  There are several  da'wah  steps taken by  Sayyid  Idrus:  (1)  he began his preaching through meeting with society's leading figures in Palu. This step opens the way for him to obtain some facilities for his preaching. As a  result,  his preaching which is traditionally carried out from house to house leads to the establishment of  Islamic schools; (2) From simple Islamic schools, he could build representative building to accommodate a  lot of students and also build orphanage.  These  schools  have  significantly  increased  until today; (3) He implemented some systems either in student admission as an object of da'wah (mad'u), system   of preaching, or content of preaching; (4) He carried out da'wah through modernizing education; (5) He conducted educational training for students and cadre formation  at the national or international levels.